A Novel Microdevice for Rapid Neutrophil Purification and Phenotyping in Type 2 Diabetes Mellitus. Issue 6 (23rd November 2017) - Tay, Hui Min; Dalan, Rinkoo; Li, King Ho Holden; Boehm, Bernhard O.; Hou, Han Wei
Abstract: Neutrophil dysfunction is strongly linked to type 2 diabetes mellitus (T2DM) pathophysiology, but the prognostic potential of neutrophil biomarkers remains largely unexplored due to arduous leukocyte isolation methods. Herein, a novel integrated microdevice is reported for single‐step neutrophil sorting and phenotyping (chemotaxis and formation of neutrophil extracellular traps (NETosis)) using small blood volumes (fingerprick). Untouched neutrophils are purified on‐chip from whole blood directly using biomimetic cell margination and affinity‐based capture, and are exposed to preloaded chemoattractant or NETosis stimulant to initiate chemotaxis or NETosis, respectively. Device performance is first characterized using healthy and in vitro inflamed blood samples (tumor necrosis factor alpha, high glucose), followed by clinical risk stratification in a cohort of subjects with T2DM. Interestingly, "high‐risk" T2DM patients characterized by severe chemotaxis impairment reveal significantly higher C‐reactive protein levels and poor lipid metabolism characteristics as compared to "low‐risk" subjects, and their neutrophil chemotaxis responses can be mitigated after in vitro metformin treatment. Overall, this unique and user‐friendly microfluidics immune health profiling strategy can significantly aid the quantification of chemotaxis and NETosis in clinical settings, and be further translated into a tool for risk stratification and precision medicine methods in subjects with metabolic diseases such as T2DM. Abstract : Rapid neutrophil profiling using a drop of blood is imperative for point‐of‐care risk stratification and precision medicine approaches in type 2 diabetes mellitus. Herein, a novel integrated neutrophil purification and phenotyping (chemotaxis and formation of neutrophil extracellular traps) microfluidic device is developed and clinically validated to demonstrate the prognostic potential of neutrophil biomarkers.